2014
DOI: 10.4490/algae.2014.29.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of green tide-forming species in the Yellow Sea

Abstract: Green tides occur every year in the Yellow Sea (YS), and numerous investigations are proceeding on various aspects of the phenomenon. We have identified bloom-forming species collected from diverse locations in the YS using morphological traits and the chloroplast gene for the large subunit of ribulose-1,5-bisphosphate carboxylase (rbcL). Morphological and rbcL sequence data analyses characterized the blooming species on both sides of the YS as belonging to the Ulva linza-procera-prolifera (LPP) complex clade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Historically the identification of Ulva species in Korea has been conducted almost entirely based on morphology, and only a few studies have employed molecular analysis of this genus (Bae and Lee 2001, Kang et al 2014. Kang et al (2019) reported the proportional occurrences of Ulva species using molecular approaches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Historically the identification of Ulva species in Korea has been conducted almost entirely based on morphology, and only a few studies have employed molecular analysis of this genus (Bae and Lee 2001, Kang et al 2014. Kang et al (2019) reported the proportional occurrences of Ulva species using molecular approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Although U. australis is also a bloom-forming species, it is not a free-floating, but requires attachment around Jeju Island. On the other hand, green tides in the Yellow Sea of the Korean Peninsula consisted predominantly of U. linza and rarely of U. compressa or U. prolifera (Kang et al 2014). U. linza is characterized by strap-shaped, sheet-like thalli with ruffled blade margins, but it shows considerable phenotypic plasticity induced by the environment (Brodie et al 2007, Belton et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, (Ulva) , (golden tide) (Sargassum) (Norkko and Bonsdorff, 1996). 2008 6 (Pang et al, 2010;Kang et al, 2014 (Higgins et al, 2008).…”
mentioning
confidence: 99%